Associations of vitamin D with coronary revascularization and heart rate variability in hypertensive patients - Li, Zongbin; Zou, Yuting; Li, Ruizhe; Zhang, Minglei (Frontiers in Cardiovascular Medicine, 2025)
BackgroundEven though substantial evidence has found that vitamin D deficiency correlates to risk factors for cardiovascular disease (CVD), few studies have shown how vitamin D affects coronary revascularization and heart rate variability (HRV). We aimed to explore the connection between vitamin D levels with coronary revascularization and HRV in hypertensive patients.MethodsA total of the 250 eligible participants with hypertension hospitalized at the Department of Cardiology, Sixth Medical Center of Chinese PLA General Hospital was consecutively recruited. The status of vitamin D is measured utilizing serum 25-hydroxyvitamin D3 [25(OH)D3] concentrations. The primary endpoints were defined as patients undergoing coronary revascularization treatment. The secondary endpoints were defined as the variation in HRV. HRV indices were recorded in participants using a 24-h Holter electrocardiogram (ECG). In addition, direct renin concentrations and plasma aldosterone concentrations were measured in the supine and standing positions.ResultsIn the study, 165 eligible patients assigned to the vitamin D deficiency [25(OH)D3 < 20 ng/ml] group and 85 to the vitamin D non-deficiency[25(OH)D3 ≥ 20 ng/ml] group. In both univariate logistic regression analysis (OR: 2.46, 95% CI: 1.06–5.68; P = 0.036) and multivariate logistic regression analysis (OR: 2.54, 95% CI: 1.02–6.33; P = 0.046), the 25(OH)D3 < 20 ng/ml demonstrated to be a significant risk factor of primary endpoints for those hypertensive patients. Receiver operating characteristic curve (ROC) analysis showed the multivariable-adjusted model for predicting primary endpoints in patients with hypertension, with an area under the curve (AUC) of 0.73 (95% CI: 0.64–0.82, p < 0.001). Regarding secondary endpoints, the HRV indexes such as standard deviation of normal-to-normal (NN) intervals (SDNN) (P = 0.04), standard deviation of the averages of NN intervals in all 5-min segments (SDANN) (P = 0.03), and Triangle indexes values (P = 0.02) were significantly different in the two groups. Finally, we observed that hypertensive patients with vitamin D deficiency had significantly greater aldosterone and aldosterone-to-renin ratio (ARR) values than those having vitamin D non-deficiency.ConclusionVitamin D deficiency was prevalent in hypertensive patients and was independently associated with the risk of coronary revascularization. Vitamin D deficiency also affects HRV and ARR values in hypertensive patients.